Hardware/Software Codesign in a Compact Ion Mobility Spectrometer Sensor System for Subsurface Contaminant Detection. (15th January 2008) - Loo, Sin Ming; Cole, Jonathan P.; Gribb, Molly M.
Abstract : A field-programmable-gate-array-(FPGA-) based data acquisition and control system was designed in a hardware/software codesign environment using an embedded Xilinx Microblaze soft-core processor for use with a subsurface ion mobility spectrometer (IMS) system, designed for detection of gaseous volatile organic compounds (VOCs). An FPGA is used to accelerate the digital signal processing algorithms and provide accurate timing and control. An embedded soft-core processor is used to ease development by implementing nontime critical portions of the design in software. The design was successfully implemented using a low-cost, off-the-shelf Xilinx Spartan-III FPGA and supporting digital and analog electronics.